2011
DOI: 10.1007/s12253-011-9389-4
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin Expression as a Prognostic Marker in Colorectal Adenocarcinoma

Abstract: Ezrin protein acts in the regulation of cytoskeletal and directly influences survival and tumor progression; there is an increase in its expression in metastatic cells and tissues in several types of cancer including colorectal cancer. 250 Patients with colorectal cancer submitted to surgery from 1995 to 2002. Protein expression was carried through by Tissue Micro Array immunohistochemical tests of paraffined neoplasic tissues and associated with clinical variables. Differentiation degree, lymph node invasion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
6
22
0
Order By: Relevance
“…This observation is consistent with the results of previous studies that also reported a significant correlation between higher ezrin expression and a lower survival rate, such as in carcinoma of head and neck, tongue, esophagus, breast, cutaneous and uveal melanoma, and soft tissue sarcoma (Saito et al, 2013). neck cancers revealed that increased cytoplasmic expression was associated with tumors of a more invasive nature, and therefore led to a lower survival rate (Ohtani et al, 1999;Tokunou et al, 2000;Patara et al, 2011). Our results are in line with these findings; the univariate analysis (2006) and Fazioli et al (1993) discovered that the translocation of ezrin from the membrane into the cytoplasm was associated with increased tumor invasiveness.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with the results of previous studies that also reported a significant correlation between higher ezrin expression and a lower survival rate, such as in carcinoma of head and neck, tongue, esophagus, breast, cutaneous and uveal melanoma, and soft tissue sarcoma (Saito et al, 2013). neck cancers revealed that increased cytoplasmic expression was associated with tumors of a more invasive nature, and therefore led to a lower survival rate (Ohtani et al, 1999;Tokunou et al, 2000;Patara et al, 2011). Our results are in line with these findings; the univariate analysis (2006) and Fazioli et al (1993) discovered that the translocation of ezrin from the membrane into the cytoplasm was associated with increased tumor invasiveness.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…The active form is physiologically localized in the membrane and the inactive form in the cytoplasm (Bretscher et al, 2002). Whereas an increased cytoplasmic ezrin expression was found in aggressive colorectal carcinomas (Patara et al, 2011) and lung adenocarcinomas (Tokunou et al, 2000), an increased membranous expression was detected in endometrioid adenocarcinoma (Ohtani et al, 1999). Tumor cells which had a strong ezrin expression concurrently showed an intensive loss of cell-cell contacts (Mangeat et al, 1999) and an increased expression of genes that promote cell migration, cell invasion and inhibition of apoptosis, thus facilitating carcinogenesis and metastasis (Curto and McClatchey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As they persistently have been found upregulated in CRC, the decreased expression seems to distinguish this premalignant state from both normal, inflamed, and cancerous tissue in the colon. [38][39][40][41] Thus, especially LAMC2 may constitute a potential biomarker of preneoplastic lesions in patients with UC. However, the downregulation of LAMC2, ITGA6, and EZR seen in cohort 1 was not validated in cohort 3, which signifies one of the weaknesses in this study; cohort 3 was based on a relative low number of patients and FFPE biopsies, and the results have to be interpreted with this matter in mind.…”
Section: Discussionmentioning
confidence: 99%
“…The materials and methods used in this study have been described previously 11,24,25. Sections (4-µm thick) from the TMA blocks were transferred to poly-L-lysine-coated glass slides and incubated in a dry oven, at 60℃ for 1 hour.…”
Section: Methodsmentioning
confidence: 99%